2006
DOI: 10.1016/j.jvs.2006.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Management of aneurysms involving branches of the celiac and superior mesenteric arteries: A comparison of surgical and endovascular therapy

Abstract: Endovascular management of visceral aneurysms is an effective means of treating aneurysms involving branches of the celiac and superior mesenteric arteries and is particularly useful in patients with comorbidities, including cancer. It is associated with a decreased length of stay in the elective setting, and failure of primary treatment can often be successfully managed percutaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
164
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(173 citation statements)
references
References 23 publications
2
164
0
7
Order By: Relevance
“…technique can be particularly beneficial for treatment of VAA in patients with comorbidities, 7,8) whereas, surgical resection of the aneurysm can achieve the prevention of rupture with certainty, and is also an effective treatment. 9) In this case, surgical resection of the aneurysm was performed but endovascular treatment was not for the following reason: subacute phase dissecting lesions remained at the abdominal aorta, especially around the orifices of the celiac artery, SMA and renal arteries.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…technique can be particularly beneficial for treatment of VAA in patients with comorbidities, 7,8) whereas, surgical resection of the aneurysm can achieve the prevention of rupture with certainty, and is also an effective treatment. 9) In this case, surgical resection of the aneurysm was performed but endovascular treatment was not for the following reason: subacute phase dissecting lesions remained at the abdominal aorta, especially around the orifices of the celiac artery, SMA and renal arteries.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…4,[6][7][8]21 For example, Marone et al have reported that the overall 10-year survival rate after the treatment of VA is 68%. 8 …”
Section: Discussionmentioning
confidence: 99%
“…4,5 SMAA is commonly located in the proximal part of the SMA, 4,6 which is suitable for endovascular treatment (ET). 7,8 Here, we report a rare case of SMAA associated with Takayasu's arteritis (TA), located in the distal part of the SMA and treated by surgical resection using the mini-laparotomy method.…”
mentioning
confidence: 99%
“…Endovascular options include embolization of the aneurysms or stent graft deployment 8 . Some anatomical conditions are required though for technical feasibility of these procedures (saccular aneurysm with a narrow neck, fusiform aneurysm with adequate collateral flow, aneurysm of a vessel supplying an organ that has multiple arterial sources).…”
Section: Treatmentmentioning
confidence: 99%
“…Some anatomical conditions are required though for technical feasibility of these procedures (saccular aneurysm with a narrow neck, fusiform aneurysm with adequate collateral flow, aneurysm of a vessel supplying an organ that has multiple arterial sources). 8 Even though this less aggressive option plays an important role in high risk surgical candidates, it has its potential complications such as visceral ischemia resulting in sacrifice of the involved visceral vessel, end-organ thrombosis, and late-term vessel recanalization. Trans catheter embolization is the most popular endovascular intervention performed despite the potential risk of visceral ischemia and organ infarction.…”
Section: Treatmentmentioning
confidence: 99%